The effect of tillage system and nitrogen fertilization on yield and yield components of winter spelt cultivars (Triticum aestivum ssp. spelta L.) - Hury, Grzegorz; Stankowski, Sławomir; Jaroszewska, Anna; Michalska, Bożena; Gibczyńska, Marzena (Polish Journal of Agronomy, 2020)
The aim of the present paper is to assess the effect of cultivation systems and varied nitrogen fertilisation doses on yield and yield components of two cultivars and one strain of winter spelt. The experiment was conducted on soil is classified as Haplic Cambisol. Three factors were compared in the course of the experiment: factor I – 2 cultivation systems: reduced tillage and conventional cultivation, factor II – 4 nitrogen fertilisation levels, factor III – cultivar/strain. The plants under analysis were two cultivars of winter spelt: German ‘Frankenkorn’ and Swiss ‘Oberkulmer Rotkorn’ and strain STH 12. There was no significant difference regarding winter spelt grain yield depending on the cultivation system. Nitrogen fertilisation caused a significant increase in yield to a certain threshold which, when exceeded, resulted in a decrease of grain yield. The highest yield was obtained for STH 12 strain. With respect to thousand grain weight, number of ears per m2, number of grains yield per ear, and ear yield, there was a significant relationship with the cultivar factor. SPAD values showed no differences between cultivars. The method of cultivation (conventional vs. reduced tillage) did not show differences for the four analysed yield components and SPAD of winter spelt.